212Pb in targeted radionuclide therapy: a review - Jarred Michael Scaffidi-Muta; Andrew David Abell (EJNMMI Radiopharmacy and Chemistry)
Abstract Background The selective delivery of α-emitting radionuclides is emerging as a highly effective form of cancer therapy. With a short range and high cytotoxicity, α-particles can selectively kill cancerous cells whilst minimising harm to surrounding healthy tissue. As the parent of the α-emitter 212Bi, 212Pb has seen increasing therapeutic use on account of its favourable chemistry, half-life, and decay properties. This review comprehensively discusses the clinical development of 212Pb in recent years, particularly its production, chelation chemistry, and therapeutic adoption. Main body Improvements in generator technology and supply have overcome the historically limited availability of 212Pb, enabling a surge of research in the field. Numerous bifunctional chelators have since been developed, which enable facile conjugation of 212Pb to a plethora of tumour targeting carriers. Advancements in nuclear imaging techniques, and the use 203Pb as an imaging surrogate, have enabled accurate biodistribution and dosimetry information to inform preclinical studies. These factors have attracted considerable commercial interest in 212Pb, culminating in the rapid translation of this radionuclide into the clinic, where it is being investigated in the treatment of a range of malignancies. Conclusion Radiotherapy with 212Pb has shown enormous promise in preclinical and clinical studies. While challenges still remain before 212Pb can be more widely adopted, remarkable progress has been made in addressing these. At present, the therapeutic potential of 212Pb is only beginning to be realised.